Associação entre otalgia, zumbido, vertigem e hipoacusia com desordens temporomandibulares - Urban, Vanessa Migliorini; Neppelenbroek, Karin Hermana; Pavan, Sabrina [UNESP]; de Alencar Júnior, Francisco Guedes Pereira [UNESP]; Jorge, Janaina Habib [UNESP]; Almilhatti, Hércules Jorge (My University, 2009)
Because nonespecific symptoms and signs are associated with others well-established in the temporomandibular disorders, it is difficult for the clinician to decide what symptoms and signs should be considered during the diagnosis and the treatment plan. Therefore, the aim of this literature review was to evaluate the prevalence of aural symptoms (otalgias, tinnitus, dizziness and deafness) in patients with orofacial pain. Although several hypotheses have been proposed to explain the association between aural symptoms and temporomandibular disorders, the results of the previous studies differed in magnitude. For this reason, it is difficult to establish the prevalence of these aural symptoms concomitantly with temporomandibular disorders. Moreover, such relationship does not necessarily imply a cause-effect relationship. Because of the diagnosis complexity, different treatments must be considered, so the nonespecific symptoms of temporomandibular disorders can be effectively controlled as well. It is crucial for the the clinician to be aware of the possible etiology of aural symptoms, so he should determine if such symptoms may be associated with temporomandibular disorders and thus include them in the treatment.
Association between otalgia, tinnitus, vertigo and hypoacusia, with temporomandibular disorders
Keywords: Craniomandibular disorders; Earache; Hearing loss; Tinnitus; Vertigo